Information support of logistics methods of resource management during rolling stock maintenance - Mykola Hnennyi; Mykhailo Kapitsa; Liubov Pryvalova (Cхід, 2013)
Possibility of normative method upgrading of material flows planning on railway transport being described in the article. Authors propose to apply logistic approach and create integrated effective system for regulation and control of material flows. This aim is tightly connected with solving of such problems as: correspondence of material and informational flows; controlling of material flow and transfer of data about it to the only center; definition of: strategy of goods physical movement technology and management methods of goods movement operations; setting of rates; definition of manufacturing volumes; warehousing and etc. System mechanism of regulation and control of material and informational flows during repairs of fixed assets on railway enterprises was described. Measures for conversion into such system of work and structured informational needs of railway managers of different levels are developed. Being proved that account of informational needs of different levels managers will give possibility to make more corrective decisions, decrease material costs and save quality parameters of branch enterprises and railway transport on the whole.